Tumors establish resistance to immunotherapy by regulating Treg recruitment via CCR4. Issue 2 (26th November 2020) - Marshall, Lisa A; Marubayashi, Sachie; Jorapur, Aparna; Jacobson, Scott; Zibinsky, Mikhail; Robles, Omar; Hu, Dennis Xiaozhou; Jackson, Jeffrey J; Pookot, Deepa; Sanchez, Jerick; Brovarney, Martin; Wadsworth, Angela; et al.
Abstract : Background: Checkpoint inhibitors (CPIs) such as anti-PD(L)-1 and anti-CTLA-4 antibodies have resulted in unprecedented rates of antitumor responses and extension of survival of patients with a variety of cancers. But some patients fail to respond or initially respond but later relapse as they develop resistance to immune therapy. One of the tumor-extrinsic mechanisms for resistance to immune therapy is the accumulation of regulatory T cells (Treg ) in tumors. In preclinical and clinical studies, it has been suggested that tumor trafficking of Treg is mediated by CC chemokine receptor 4 (CCR4). Over 90% of human Treg express CCR4 and migrate toward CCL17 and CCL22, two major CCR4 ligands that are either high at baseline or upregulated in tumors on CPI treatment. Hence, CCR4 antagonism has the potential to be an effective antitumor treatment by reducing the accumulation of Treg into the tumor microenvironment (TME). Methods: We developed in vitro and in vivo models to assess Treg migration and antitumor efficacy using a potent and selective CCR4 antagonist, CCR4-351. We used two separate tumor models, Pan02 and CT26 mouse tumors, that have high and low CCR4 ligand expression, respectively. Tumor growth inhibition as well as the frequency of tumor-infiltrating Treg and effector T cells was assessed following the treatment with CCR4 antagonist alone or in combination with CPI. Results: Using a selective and highly potent, novel small molecule inhibitor of CCR4, we demonstrate that migration of CCR4 + Treg into the tumor drives tumor progression and resistance to CPI treatment. In tumor models with high baseline levels of CCR4 ligands, blockade of CCR4 reduced the number of Treg and enhanced antitumor immune activity. Notably, in tumor models with low baseline level of CCR4 ligands, treatment with immune CPIs resulted in significant increases of CCR4 ligands and Treg numbers. Inhibition of CCR4 reduced Treg frequency and potentiated the antitumor effects of CPIs. Conclusion: Taken together, we demonstrate that CCR4-dependent Treg recruitment into the tumor is an important tumor-extrinsic mechanism for immune resistance. Blockade of CCR4 led to reduced frequency of Treg and resulted in increased antitumor activity, supporting the clinical development of CCR4 inhibitors in combination with CPI for the treatment of cancer. Statement of significance: CPI upregulates CCL17 and CCL22 expression in tumors and increases Treg migration into the TME. Pharmacological antagonism of the CCR4 receptor effectively inhibits Treg recruitment and results in enhanced antitumor efficacy either as single agent in CCR4 ligand high tumors or in combination with CPIs in CCR4 ligand low tumors.